High and Stable Human Immunodeficiency Virus Prevalence Among Transwomen With Low Income Recruited With Respondent-driven Sampling, San Francisco, 2010–2016. Issue 2 (February 2019) - Raymond, Henry F.; Wilson, Erin C.; Packer, Tracey; Ick, Theresa; Lin, Jess; McFarland, Willi
Abstract : Background: Studies have documented high human immunodeficiency virus (HIV) prevalence among transwomen in the United States; however, to our knowledge, no studies have documented trends in HIV prevalence in this population. Methods: We used respondent-driven sampling to sample transwomen in San Francisco for 3 HIV prevalence and behavioral surveys in 2010, 2013, and 2016. Our analysis of point estimates and trends were weighted for the sampling method. Results: Human immunodeficiency virus prevalence by serological testing in the survey was 38.8% (95% confidence interval [CI], 32.4–45.2), 33.7% (95% CI, 25.9–41.5), and 31.6% (95% CI, 12.2–38.1) in 2010, 2013, and 2016, respectively. Disparities in higher HIV prevalence by black, Latino, and Asian race/ethnicity and lower education level persisted through 2016. Conclusions: Based on a statistical test for trend, HIV prevalence among transwomen has remained high and stable from 2010 to 2016. Human immunodeficiency virus infection is still highest at 31.6% compared to any other group in San Francisco. We also observed that older transwomen had significantly higher odds of living with HIV than younger women over the last 2 waves of data collection. Taken together, these trends suggest that there is declining incidence of new HIV infections among low-income transwomen in San Francisco. Moreover, among transwomen, HIV disproportionately affects transwomen of color. Abstract : Human immunodeficiency virus prevalence among transwomen has remained high and stable from 2010 to 2016. Older transwomen had higher odds of HIV infection. These trends suggest declining incidence of new human immunodeficiency virus infections among transwomen in San Francisco.